2009
DOI: 10.1002/ange.200901618
|View full text |Cite
|
Sign up to set email alerts
|

Modular Peptide Growth Factors for Substrate‐Mediated Stem Cell Differentiation

Abstract: Natural proteins are often multifunctional, and therefore capable of activating cell surface receptors, and also binding with high affinity and specificity to natural extracellular matrices (ECMs). To achieve these diverse functions, a strategy commonly employed by nature involves creating modular proteins, in which distinct domains within a single protein are designed to enable either cell signaling or ECM binding. For example, modular proteins such as osteocalcin (OCN) and bone sialoprotein (BSP) contain a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…All peptides investigated in this study were prepared following reported protocols with minor modifications. [13,14] Detail experimental information about materials and methods is described in the Supporting Information. Binding affinity and release kinetics of HABPs with HA were evaluated by incubating various amounts of peptides (0-20 mm) with HA (5 mg mL À1 ) solution.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All peptides investigated in this study were prepared following reported protocols with minor modifications. [13,14] Detail experimental information about materials and methods is described in the Supporting Information. Binding affinity and release kinetics of HABPs with HA were evaluated by incubating various amounts of peptides (0-20 mm) with HA (5 mg mL À1 ) solution.…”
Section: Methodsmentioning
confidence: 99%
“…CD spectra were collected to confirm conformational changes of HABPs in the absence or presence of HA. [7,13] For binding competition assay of HABP-19 and PAM, HA (5 mg mL À1 ) was incubated in mixtures that were composed of HABP-19 (10 mm) and PAM (0-200 mm). Cy-HABP-19 was engineered by conjugating Cy5.5 with Cys-containing HABP-19 peptide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent experience with nanostructured mineral coatings that bind to biologics provides one example of the utility of a modular approach. [124][125][126][127][128] We have also developed molecular coatings that can induce bone formation, 108,[128][129][130][131] and the interaction between the osteoinductive molecule and the scaffold can be used to dictate the release rate. In each case, the biologics delivery is decoupled from device physical properties, thus allowing for independent optimization of each component in a modular scaffold.…”
mentioning
confidence: 99%